(untitled) (Fourth World Journal, 2020)
Within the course of the past decades, many achievements have been made with reference to indigenous rights standards, primarily through indigenous engagement and dedication within global society. After 50 years of active participation in the global arena, indigenous rights movements continue to gain momentum transforming into one of “the most visible civil society grouping across the UN” (Morgan, 2011,p.2). As a result of adoption of international standards and guidelines in addition to the establishment of institutions that specifically target the concerns of indigenous people, today indigenous peoples are more mobilized than any other time. With the notable exception (among the Arctic states) of the Russian Federation where despite a rather promising beginning of professional indigenous activism in the early 2000s, Russian indigenous groups saw even further division — yet more separate paths in contrast to international indigenous development (Eckert, 2012). While the protection of indigenous peoples’ rights and interests is becoming an important global goal and the essential sphere of international cooperation, domestically there are still some fundamental imbalances in power, rights and inclusion of indigenous peoples in decision-making process. This article is an attempt to raise fundamental questions about the nature of contemporary Russian policy towards its indigenous population and shed light upon the various characteristics that have come to define Russia’s response to indigenous problematics.